THE ROLE OF THE PRINCIPAL AS A LEADER IN IMPROVING TEACHER PERFORMANCE - herayati herayati (Sean Institute, 2022)
This study aims to describe the role of the principal as a leader in improving teacher performance. The principal is the highest position in the school organization. The principal acts as a school leader and in the school organizational structure his position is at the top. The principal as a leader must be able to provide guidance and supervision, improve the ability of educators, open two-way communication, and delegate tasks. Thus the principal plays a very important role in improving teacher performance. Teacher performance is the result of teacher work that can be achieved by a teacher in educational institutions in accordance with their duties and responsibilities. In the learning process the teacher is seen as having an important role, especially in helping students to develop their potential in cognitive, affective and psychomotor abilities, the teacher also seeks to arouse curiosity, encourage independence and accuracy of intellectual logic, and create conditions for success in learning This value is included in the